2019
DOI: 10.30650/ajte.v1i2.212
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Students’ Vocabulary Mastery By Using Kahoot At Holmesglen Partnering With University of Muhammadiyah Tangerang

Abstract: The present study investigated the use of Kahoot as the free game-based learning platform which provided the students with ongoing feedback on their learning progresses. Reviewing the students’ vocabulary was the focus of this study. Unlike summative test that tended to have formal assessment, Kahoot provided a learning with engagement and responsive feedback both students and teacher. In term of student’s vocabulary mastery, Kahoot was the learning model of this study. Blended learning was applied technically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Enjoyable assessments could help students with test anxiety and gave them assurance about their abilities and boost their self-esteem (Johns, 2015). These results concurred with the findings by Al Manar et al (2019), Sartini (2020), Chachra et al (2019) and who found that Kahoot could enhance vocabulary learning and motivated students to learn English vocabulary.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Enjoyable assessments could help students with test anxiety and gave them assurance about their abilities and boost their self-esteem (Johns, 2015). These results concurred with the findings by Al Manar et al (2019), Sartini (2020), Chachra et al (2019) and who found that Kahoot could enhance vocabulary learning and motivated students to learn English vocabulary.…”
Section: Discussionsupporting
confidence: 92%
“…In line with this context, a recent study regarding Kahoot was conducted by Al Manar et al (2019) to investigate whether the students' interest in using technology could be used to improve students' learning performance. It was found by the researcher from the interview that the students mostly had difficulties in memorizing and using vocabulary in their daily conversation.…”
Section: Implementing Technology In Teaching Technical Vocabularymentioning
confidence: 99%
“…Students who answer the option strongly agree was reached 81 %. The finding collaborated with the study of (Almanar, 2019) that students are more interested in using technology especially using Kahoot in learning English. It was reached 58.33 % who were interested in using Kahoot in the learning process.…”
Section: Discussionmentioning
confidence: 57%
“…The other previous research by Almanar, M. (2019) entitled "Reviewing Students' Vocabulary Mastery By Using Kahoot At Holmesglen Partnering With University of Muhammadiyah Tangerang." that the purpose was reviewing the students' vocabulary and also discusses the impact for both learners' involvement when using technology and their learning motivation and achievement.…”
Section: Findings and Discussionmentioning
confidence: 99%